Application of fuzzy logic method in electric charge tomography as a flow regime identifier - Rahmat, Mohd. Fua'ad (Penerbit UTM, 2010)
Transportation of bulk solid materials over long distance from one station to another is gradually becoming routine in industrial trade. The conveying of bulk solids is commonly carried out all the way through a closed conduit with water or air as the conveying medium. Material handling by pneumatic conveying can be found in wide applications particularly industries dealing with power generation, food processing, steel making, pharmaceuticals, solid waste treatment, chemical and many others.